Transformational Leadership of the Principal in Improving the Quality of Human Resources at State Integrated Junior High Schools in Sigi Regency, Indonesia - Noprianto Noprianto; Azma Azma; Sofyan Bachmid (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2026)
This study examines the transformational leadership of the principal in improving the quality of human resources at SMP Satu Atap Negeri 14 Sigi using a qualitative case study approach. Data were collected through observations, interviews, and documentation involving the principal, teachers, educational staff, and the school committee. The findings show that the principal implemented transformational leadership through a clear vision and mission, motivational support, collaborative work culture, continuous professional development, and individualized attention to staff needs and potential. These practices contributed to improved teacher professionalism, staff performance, discipline, and the creation of a conducive and quality-oriented school environment. The study concludes that transformational leadership plays a significant role in enhancing the quality of human resources in schools